Comparative Evaluation of Fluoride Release from Glass Ionomer Cement Modified with Different Concentrations of Chitosan: An in vitro Study - Jaganath, Bharath Makonahalli; Krishnegowda, Sahadev Chickmagarvalli; Rudranaik, Sandeep; Ajakkala, Prashanth Sharma (International Journal of Dental Materials, 2024)
Background: Restorative materials releasing fluoride are essential for caries prevention. Among the restoratives, glass ionomer cement (GIC) has a remarkable fluoride-releasing ability. Aim: To evaluate and compare the effect of three different concentrations of Chitosan-modified GIC on its fluoride-releasing properties. Materials and methods: Thirty-two disk-shaped pellets having dimensions of 10 x 2 mm were made with Restorative GIC (RX Ease, Shofu, Japan) using silicone molds. Specimens were divided into four groups based on the chitosan concentration in GIC liquid, with eight (n=8) in each. Group 1: Control (Unmodified), Group 2: 10 % Chitosan, Group 3: 20 % Chitosan, and Group 4: 30 % Chitosan. The specimens of each group were immersed in deionized water at various time intervals. Electrodes selective for fluoride ions were employed to analyze the amount of fluoride release at 1, 7, and 14 days. Analysis of variance (ANOVA) followed by Post hoc Tukey’s tests were performed for statistical analysis of the obtained data. Significance levels were set at p less than 0.05. Results: Unmodified GICs exhibited higher fluoride release compared to chitosan-modified GICs at all time points. All samples initially released a high amount of fluoride, which decreased over time. Conclusion: The addition of chitosan to GIC decreased its fluoride-releasing ability. Unmodified GIC showed better fluoride release than chitosan-modified GICs.